THE EFFECT OF RATIONAL EMOTIONAL BEHAVIOR THERAPY (REBT) ON KNOWLEDGE ABOUT THE IMPACT OF EARLY MARRIAGE ONADOLESCENT GIRLS AT THE AL-KHOLAFIYAH ISLAMICBOARDING SCHOOL IN LUMAJANG - Nora Eflin Anggela; Yessy Nur Endah Sary; Muthmainah Zakiyyah (Lppm Unan, 2026)
Background: Early marriage among adolescent girls remains a serious health and social problem, driven in part by a lack of knowledge about its negative impacts. Rational Emotive Behavior Therapy (REBT) is an effective counseling approach for changing irrational thought patterns and increasing adolescents' understanding of the consequences of their actions. With this background, the researcher aimed to explore